Percutaneous Closure of Acquired Hole- First Case Report from Bangladesh (Bangladesh Heart Journal, 2021)
Rupture sinus of Valsalva (RSOV) is an uncommon condition with a wide spectrum of presentation, ranging from an asymptomatic murmur to cardiogenic shock or even sudden cardiac death. Our case presented at 62 yrs with progressive onset of dyspnea, palpitation with deterioration of exercise capacity. Diagnosis of ruptured sinus of Valsalva was made by echocardiography, it was aneurysmal and opened into right ventricular outflow tract. Coronary artery disease was excluded by coronary angiogram. Probable cause of rupture was atherosclerosis.We closed percutaneously with ADO I device. The procedure was completed uneventfully. Patient discharged with duel antiplatelet and is on follow up.Bangladesh Heart Journal 2020; 35(2) : 155-158